PELAKSANAAN LAYANAN INFORMASI BAGI MOTIVASI BELAJAR SISWA YANG BERASAL DARI KELUARAGA BERCERAI - Nurussakinah Daulay; Ayidah Nasution; Leni Si Rezeki; Liza Anjani; Shakira Fara Indira; Yurisna Yurisna (Jurnal Edukasi : Jurnal Bimbingan Konseling, 2023)
Divorce is one of the main causes of children experiencing problems at school. Many parents do not realize that divorce will have a big impact on the child's condition. Rarely do we find children who are able to balance the problems they receive at home while continuing to carry out their school activities well. The impact of divorce also has an influence on the activity of children to want to attend school and take part in learning as they should. This is because the child is the sole victim of each parent's divorce process. And one of the causes of a child's unwillingness to attend school is because he experiences problems of confusion to choose one between his parents. Therefore, it is important to provide information services for these students, in order to help themselves in dealing with and finding solutions to these problems. This study used the observation method, namely by making direct observations at SMK Negeri 5 Medan, which was carried out for several days. The results of this study will later explain the causes of the resolution of the problems experienced by one of the students at the school by providing information services by the counseling teacher to the student concerned.